PENGARUH WHISTLEBLOWING SYSTEM DAN BUDAYA ORGANISASI TERHADAP PENCEGAHAN FRAUD PADA PERUSAAHAN DAERAH AIR MINUM WAIR PU’AN - Margaretha Ririn Novitasari; Yosefina Andia Dekrita; Thadeus Fransesco Quelmo Patty (Media Mahardhika, 2026)
This study examines the effect of the Whistleblowing System and Organizational Culture on Fraud Prevention at the Wair Pu'an Regional Water Supply Company. Fraud prevention is critical in public service organizations, as fraudulent practices undermine institutional performance, public trust, and accountability in managing public resources. Thus, implementing an effective whistleblowing system and fostering a strong organizational culture are considered essential to minimize fraud risks. A quantitative associative approach was employed, with the entire population of 80 employees used as the sample through saturated sampling. Data were collected via questionnaires and analyzed using descriptive statistics and multiple linear regression. Prior to hypothesis testing, validity, reliability, and classical assumption tests including normality, multicollinearity, and heteroscedasticity were conducted. The results demonstrate that both the Whistleblowing System and Organizational Culture have a positive and significant effect on Fraud Prevention, both partially and simultaneously. The t-test confirms that each variable independently contributes significantly, while the F-test validates their combined explanatory power. The coefficient of determination indicates that both variables account for 38.9% of the variance in fraud prevention, with the remaining 61.1% influenced by external factors not included in the model. These findings suggest that strengthening whistleblowing mechanisms and cultivating an integrity-based organizational culture are effective strategies for enhancing fraud prevention in regional public companies. The study implies that organizations should invest in transparent reporting systems and ethical culture development to reduce fraudulent behavior and improve overall governance.